A diez años de la erupción del Puyehue-Cordón Caulle - Murriello, Sandra; Barrios García, Gonzalo (Aperturas, 2023)
One sunny and cold afternoon in June 2011, the sky turned black and sand began to fall from the sky in Bariloche, Villa Traful, Villa La Angostura and surrounding areas. The Puyehue-Cordón Caulle Volcanic Complex, located in Chile, had erupted and the ashes soon reached Argentina. Surprise and uncertainty dominated the regional scenario. The affected communities had not been warned, no contingency protocols had been activated and there was no clear official communication on how to act in the event of such an occurrence. More than a decade after the event, this book addresses and presents to the reader the diverse consequences of the society-nature relationship. The starting point is the reconceptualization of the notion of natural disaster, which manifests the distancing between nature and society and has made human beings lose their ancestral fear of geological and meteorological phenomena, to consider instead the conditions of vulnerability of the Northern Patagonian region. In this way, and with the aim that the knowledge about the multiplicity of events generated by the eruption allows mitigating its negative effects, this research recovers the memory of the inhabitants and analyzes the approach strategies focused on economic, productive and social activities. In addition, detailed studies on the impact of ash on insects, biota and aquatic systems are presented.